Perbedaan Pengetahuan Mengenai Pendewasaan Usia Perkawinan Sebelum Dan Sesudah Diberikan penyuluhan Pada Siswa Di Sma Negeri 2 Tabanan - Ni Made Ayu Sariani; Made Widhi Gunapria Darmapatni; Ni Ketut Somoyani (Poltekkes Kemenkes Denpasar, 2020)
ABSTRACTEarly marriage often begins with pregnancy. This research aims to determine the difference of knowledge about the maturation age of marriage before and after given counseling to students in SMA Negeri 2 Tabanan. This study was analytic with a one-group pre-test-post-test study. Sample in this research is student of class XI which amounted 92 student. The sampling technique is stratified random sampling. The instrument used is a questionnaire of 30 questions that have been valid and reliable. Data analysis technique using Paired t Test. The results showed that the mean before giving 87,57 counseling and after counseling obtained 91,52 obtained increase of mean equal to 3,95. Based on the analysis of Paired t Test obtained p value = 0,000 0,05 the result show there is significant difference of student knowledge about maturation age of marriage before and after given counseling. Extracurricular based on reproductive health in schools is expected to be improved and students are more active in organizations in schools and follow reproductive health education activities.Keywords: Knowledge; Maturation age of marriage; Counseling